Solidarity economy in the production and commercialization improvement of typical sweets from San Basilio de Palenque, Colombia - Cano Parra, Diego Arturo; Guillén Cruz, Michael Stiven; Matiz Piza, Mayra Evelyn; Vargas Prieto, Amanda (Cooperativismo & Desarrollo, 2017)
Purpose: This research analyzes the solidarity organizations in San Basilio de Palenque, Colombia, particularly the women’s associations of this village, which produce and market regional typical sweets in an artisan manner, and economically depend on this work.Themes: This community presents economic, social and financial problems that preclude its development.Development: Given the above, the following question arises: what is the role of solidarity economy in improving the production and marketing of typical sweets from San Basilio de Palenque?Conclusions: Through a qualitative methodology applying the ethnographic method and based on life stories and biographies, it was found that solidarity organizations contribute to the reduction of poverty, improve the quality of life of the population involved and, generate development for the community where they establish. These allow low-income communities to be part of the organization’s value chain, either as consumers, producers, suppliers or partners.
Keywords: value chain; quality of life; solidarity economy; producers